Molecular mechanisms of electropuncture in cerebrovascular protection during enhanced recovery after surgery period - Mao, Yu; Yang, Lifang (Frontiers in Anesthesiology, 2023)
The core intent of enhanced recovery after surgery (ERAS) is to alleviate the perioperative stress response and postoperative complications through perioperative multimodal analgesia and intensive surgery. Previous studies have demonstrated that multiple molecular mechanisms function in improving ischemic stroke, reversing the process of ischemia reperfusion, relieving intracerebral hemorrhage and traumatic brain injury. Meanwhile, electroacupuncture (EA) has been validated with regard to its efficacy and safety in perioperative treatment, which has an important impact on rehabilitation research and ERAS development. Currently, studies have showed that EA provides a new approach for cerebrovascular protection by activating various molecular mechanisms. In this review, we display the recent progress of main molecular mechanisms of EA in ERAS from the perspectives of protecting cerebrovascular functions, in order to provide guidance for the clinical treatment.